المنجز البلاغي للسكاكي في ميزان المحدثين محمد عبد المطلب ـ أنموذجا - إسلام, ميلاط; فاطمة, صغير (جامعة الوادي university of eloued, 2023)
مر علم البلاغة ـــــ كغيره من العلوم الأخرى ـــــ بمراحل عديدة، اكتمل فيها نشأة و تطورا، فكثرت مسائله و تعددت مادته.وتاريخ هذا العلم يشهد أن استوائه علما قائما بذاته، كان على يد العلامة أبي يعقوب السكاكي(626ه) في سفره الجليل " مفتاح العلوم "، و نظرا لأهمية هذه المرحلة التي اتسمت بالتقنين و التقعيد، لهيكل الدرس البلاغي القديم، فقد تناولها المحدثون بالدرس و التمحيص. و من الدراسين البارزين الذين تتبعوا جهود السكاكي، في محاولة منهم إلى تقييم هذه الحصيلة المعرفية من التفكير البلاغي نجد محمدا عبد المطلب، لاسيما و قد تضاربت فيها أقوال الباحثين، بين مؤيد و معارض، مما كون خلافا اقتضى إعادة قراءة منه لهذه المحطة التاريخية المهمة، متبعا منهجا علميا، يقوم على الموضوعية في النظر إلى ما كتب عن السكاكي. The science of rhetoric –like other sciences – passed through many stages,it completed its emergence and development, the history of this science testifies that its leveling of a stand-alone knowledge that was carried out by the scholar abu ya’qub al-sakaki (626ah) in his great book, « miftah al-uloom » the key to science,due to the importance of this stage, which was characterized by codification and complication, to the structure of the ancient rhetorical lesson. And from the prominent academics who followed the efforts of the sakaki, in an attempt to evaluate this knowledge of rhetorical thinking, we find « mohammad abdulmutallab », especially when the statements of the researchers were conflicting, between supporters and opponents, which this created a controversy that required a re-reading of this important historical station following a scientific approach, it is based on objectivity, in looking at what is written about sakaki
مقال
Keywords: البلاغة العربية ; أبو يعقوب السكاكي ; مفتاح العلوم ; محمد عبد المطلب; arabic rhetoric; abu ya’qub al-sakaki- ; the key to science « miftah al- uloom » ; mohammed abdul muttalib